Design and Prototyping of an Information System for Corporate Social and Environmental Responsibility Monitoring and Evaluation - Faiz Ananda; Yustria Handika Siregar; Mohammad Badri (Bigint Computing Journal, 2025)
Corporate Social and Environmental Responsibility (CSER) represents a company's commitment to contributing to sustainable development. The monitoring and evaluation (monev) process of CSER program implementation is often still carried out manually, which hampers the effectiveness and accountability of reporting. This study aims to design a web-based information system for monitoring and evaluating CSER using the prototyping method. This method involves several stages: communication, quick planning, quick design, prototype development, and evaluation. The outcome of this research is an information system design that includes UML diagrams (use case, activity, sequence, class) and user interface components to support the CSER monitoring and evaluation process. The system is expected to enhance the transparency, efficiency, and accountability of corporate CSER program reporting.